2015
DOI: 10.1016/j.agrformet.2015.08.256
|View full text |Cite
|
Sign up to set email alerts
|

Emulating maize yields from global gridded crop models using statistical estimates

Abstract: The MIT Joint Program on the Science and Policy of Global Change combines cutting-edge scientific research with independent policy analysis to provide a solid foundation for the public and private decisions needed to mitigate and adapt to unavoidable global environmental changes. Being data-driven, the Program uses extensive Earth system and economic data and models to produce quantitative analysis and predictions of the risks of climate change and the challenges of limiting human influence on the environment-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 37 publications
0
35
0
Order By: Relevance
“…Blanc and Sultan (2015) and Blanc (2017) showed that the statistical emulators are overall able to replicate reasonably well the spatial patterns of yields crop projected by crop models in levels but also in term of changes overtime. However, as noted in Blanc (2017), "due to GGCM specificities, simulations are more suited to assess long-term trends in yields rather than interannual yield variability".…”
Section: Statistical Emulator Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Blanc and Sultan (2015) and Blanc (2017) showed that the statistical emulators are overall able to replicate reasonably well the spatial patterns of yields crop projected by crop models in levels but also in term of changes overtime. However, as noted in Blanc (2017), "due to GGCM specificities, simulations are more suited to assess long-term trends in yields rather than interannual yield variability".…”
Section: Statistical Emulator Characteristicsmentioning
confidence: 99%
“…Additionally, as the weather effect on crops is expected to differ across soil types, the preferred estimation strategy estimates separate weather response functions for each soil order. Validation exercises by Blanc and Sultan (2015) and Blanc (2017) showed that, in general, the emulator reproduces relatively well the temporal and spatial patterns of climate change impacts on crop yields projected by GGCMs. Areas of disagreement regarding the sign of climate change impact on yields are limited and generally observed in areas where the projected yield impact is close to zero.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations